A 24‐week study to evaluate the efficacy and safety of once‐weekly dulaglutide added on to glimepiride in type 2 diabetes (AWARD‐8). Issue 5 (19th February 2016) - Dungan, K. M.; Weitgasser, R.; Perez Manghi, F.; Pintilei, E.; Fahrbach, J. L.; Jiang, H. H.; Shell, J.; Robertson, K. E.
Abstract : Aims: To evaluate the safety and efficacy of once‐weekly dulaglutide 1.5 mg, a long‐acting glucagon‐like peptide‐1 receptor agonist, compared with placebo in patients with type 2 diabetes (T2D) on glimepiride monotherapy. Methods: This phase III, randomized (4 : 1; dulaglutide:placebo), double‐blind, placebo‐controlled, 24‐week study compared the safety and efficacy of once‐weekly dulaglutide 1.5 mg with placebo in sulphonylurea‐treated (≥half‐maximal dose, stable ≥3 months) patients (N = 300) with T2D and inadequate glycaemic control [glycated haemoglobin (HbA1c) ≥7.5 and ≤9.5% (≥58 mmol/mol and ≤80 mmol/mol)]. Analysis was carried out according to intention‐to‐treat. Results: At baseline, the mean participant age was 58 years; mean HbA1c was 8.4% (68 mmol/mol) and mean weight was 85.5 kg. Dulaglutide 1.5 mg was superior to placebo at 24 weeks for HbA1c reduction from baseline with a between‐group HbA1c difference of −1.3% [95% confidence interval (CI) −1.6, −1.0] or ‐14 mmol/mol (95% CI −17, −11); p < 0.001. A greater proportion of participants in the dulaglutide group reached an HbA1c level of <7.0% (53 mmol/mol) compared with placebo (55.3% vs 18.9%; p < 0.001). Dulaglutide significantly decreased fasting serum glucose from baseline compared with placebo (between‐group difference −1.86 mmol/l (95% CI −2.58, −1.14) or −33.54 mg/dl (95% CI −46.55, −20.53); p < 0.001. Weight was decreased significantly from baseline in the dulaglutide group (p < 0.001); the between‐group difference was not significant. The most common treatment‐emergent adverse events for dulaglutide 1.5 mg were gastrointestinal: nausea (10.5%), diarrhoea (8.4%) and eructation (5.9%). Total hypoglycaemia was higher with dulaglutide 1.5 mg vs placebo (2.37 and 0.07 events/participant/year, respectively; p = 0.025). No severe hypoglycaemia was reported. Conclusions: Once‐weekly dulaglutide 1.5 mg had a favourable benefit/risk profile when added to glimepiride monotherapy.